Opioid-free anesthesia: a scoping review of efficacy, safety, and implementation challenges - Pershad, Amogh; Elvir Lazo, Ofelia Loani; Wong, Robert (Frontiers in Anesthesiology, 2025)
BackgroundOpioid-free anesthesia (OFA) is a multimodal strategy to avoid intraoperative opioids and minimize associated complications, though evidence remains variable.MethodsA systematic search of PubMed and Google Scholar (2010–2025), supplemented by AI tools (Google Gemini) for earlier publications, summarized eligible studies (RCTs, cohorts, systematic reviews, and meta-analyses) comparing OFA to opioid-based anesthesia (OBA). Data were summarized following PRISMA-ScR guidelines.ResultsAcross 23 randomized controlled trials and one cohort study, OFA consistently reduced PONV, while demonstrating analgesia and recovery outcomes comparable to OBA. Hemodynamic stability was variable, with dexmedetomidine-based OFA regimens sometimes associated with increased bradycardia and hypotension. PACU stay varied, ranging from 9 min shorter to 15–35 min longer with OFA. Long-term outcome data are limited.ConclusionOFA is a feasible approach that significantly reduces PONV while maintaining comparable analgesia and recovery. However, heterogeneous protocols, small sample sizes, and scarce long-term data limit external validity. Large, multicenter trials are needed to standardize OFA protocols and clarify long-term outcomes.